Seismic Assessment of an RC Building Using Pushover Analysis - Hakim, R. A.; Alama, M. S. A.; Ashour, S. A. (Engineering, Technology & Applied Science Research, 2014)
Current research works and observations indicated that parts of the Kingdom of Saudi Arabia have low to moderate seismic regions. Major parts of buildings were designed only for gravity load and were poorly detailed to accommodate lateral loads. This study aims to investigate building performance on resisting expected seismic loadings. Two 3D frames were investigated using pushover analysis according to ATC-40. One was designed according to a design practice that considers only the gravity load and the other frame was designed according to the Saudi Building Code (SBC-301). Results showed that the building designed considering only the gravity load was found inadequate. On the other hand, the building designed according to SBC-301 satisfies the Immediate Occupancy (IO) acceptance criteria according to ATC-40.